LANDSCAPE OF THE CARPATHIAN LAND IN THE WORKS OF ARTISTS OF UKRAINE AND THE WORLD, ITS EDUCATIONAL AND UPBRINGING SIGNIFICANCE - Hnatiuk, Mykhailo (Mountain School of Ukrainian Carpaty, 2020)
The article covers the history of landscape development – one of the most emotional genres of fine arts, which has a special impact on the human personality. The object of the artist's image is architecture and its natural surroundings on the plains, in the mountains and at sea. The practice of painting outdoors (open air) has long been a mandatory component of the training of artists-teachers. At the same time, the painting of plants (flowers, trees), clouds, huts and the landscape in general is provided by the program of fine arts of primary school.